2003
DOI: 10.4049/jimmunol.171.7.3533
|View full text |Cite
|
Sign up to set email alerts
|

DNA Fragments of the Human 60-kDa Heat Shock Protein (HSP60) Vaccinate Against Adjuvant Arthritis: Identification of a Regulatory HSP60 Peptide

Abstract: Adjuvant arthritis (AA) is induced by immunizing Lewis rats with Mycobacterium tuberculosis suspended in adjuvant. The mycobacterial 65-kDa heat shock protein (HSP65) contains at least one epitope associated with the pathogenesis of AA: T cell clones that recognize an epitope formed by aa 180–188 of HSP65 react with self-cartilage and can adoptively transfer AA. Nevertheless, vaccination with HSP65 or some of its T cell epitopes can prevent AA by a mechanism that seems to involve cross-reactivity with the self… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
90
0
6

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 84 publications
(99 citation statements)
references
References 39 publications
3
90
0
6
Order By: Relevance
“…Here we describe NPs designed to coadminister a tissue specific antigen (i.e., MOG ) and an AhR ligand (i.e., ITE) to induce tolerogenic APCs that promote the differentiation of CNS-specific Tregs and suppress the development of EAE. Methods based on DNA vaccination (33,34), oral (35), nasal (36), and transdermal (37) tolerization, or administration of antigen coupled to red blood cells (38) have also been developed to expand antigen-specific Tregs, and their translational relevance is now being investigated in clinical trials. However, compared with other methods for antigen delivery, an advantage of NPs is their ability to codeliver target antigens in combination with well-defined tolerogenic small molecules to control APC activity.…”
Section: Discussionmentioning
confidence: 99%
“…Here we describe NPs designed to coadminister a tissue specific antigen (i.e., MOG ) and an AhR ligand (i.e., ITE) to induce tolerogenic APCs that promote the differentiation of CNS-specific Tregs and suppress the development of EAE. Methods based on DNA vaccination (33,34), oral (35), nasal (36), and transdermal (37) tolerization, or administration of antigen coupled to red blood cells (38) have also been developed to expand antigen-specific Tregs, and their translational relevance is now being investigated in clinical trials. However, compared with other methods for antigen delivery, an advantage of NPs is their ability to codeliver target antigens in combination with well-defined tolerogenic small molecules to control APC activity.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that CD4 ϩ regulatory T cell responses may be induced through interaction with certain T cell markers loosely and collectively called ''ergotopes'' (7,11,12). There have been some indications that T cell activation molecules such as IL-2 receptor and heat-shock protein 60 may be among candidate ergotopes (11)(12)(13)(14). It has been a topic of great interest to characterize the nature and functional properties of human CD4 ϩ regulatory T cell responses induced by T cell vaccination in clinical trials because the findings would have direct implication in the understanding of the potential therapeutic role of T cell vaccination in human autoimmune conditions.…”
Section: Mmunization With Inactivated Autoreactive T Cells (T Cell mentioning
confidence: 99%
“…This proposition is further supported by the finding that the challenge of naive LEW rats with a low nonarthritogenic dose of DDA leads not only to protection against subsequent disease triggered by injection of a higher arthritogenic dose of DDA, but also to spontaneous induction of T cell response to one of the above-mentioned peptides of Rhsp65, peptide 213-227. However, considering that our pepscan consists of a limited number of Rhsp65 peptides, it is likely that other yet undefined epitopes within Rhsp65, which might be similar to that within human hsp60 (32,33), might also contribute to regulation of acute DIA. The above results are supported by the observations in the AA model (32,33,50) and those in patients with juvenile chronic arthritis (51) regarding the role of self mammalian hsp65 in regulation of arthritis.…”
Section: Discussionmentioning
confidence: 99%
“…However, considering that our pepscan consists of a limited number of Rhsp65 peptides, it is likely that other yet undefined epitopes within Rhsp65, which might be similar to that within human hsp60 (32,33), might also contribute to regulation of acute DIA. The above results are supported by the observations in the AA model (32,33,50) and those in patients with juvenile chronic arthritis (51) regarding the role of self mammalian hsp65 in regulation of arthritis. In addition, LEW rats with DIA develop an Ab response to Rhsp65.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation